Patient and medical barriers preclude uptake of tamoxifen preventative therapy in women with a strong family history. (April 2017) - Skandarajah, Anita R.; Thomas, Susan; Shackleton, Kylie; Chin-Lenn, Laura; Lindeman, Geoffrey J.; Mann, G. Bruce
Abstract: Aims: To assess the eligibility, uptake and impediments to tamoxifen use in high-risk women attending a risk management clinic due to family history. Patients and methods: All patients with a germline mutation in a cancer predisposing gene or at high genetic risk (based on family history) attending a Breast and Ovarian cancer risk management clinic from February 2014 to May 2015 received both verbal and written evidence-based information on preventive therapy and were recommended to consider endocrine prevention if not contraindicated. Endocrine therapy initiation, use and cessation were captured. Patient eligibility was analysed and reasons for declining, ceasing or contraindications for medication use were recorded. Results: During the study period, 237 women were seen over 305 consultations for breast surveillance and preventative therapy discussion. They comprised 38 BRCA1 and 42 BRCA2 mutation carriers, 4 with Peutz-Jegher syndrome, 153 with a strong family history. Their median age was 39.4 years. Endocrine preventative was considered and discussed with all but 19 women. Of the remaining 218, 34 chose bilateral prophylactic mastectomy, while endocrine preventative was not recommended in 50 women due to contraindications and 25 women declined treatment due to their intention to fall pregnant. In 118 patients who remained eligible, 18.6% (22) tried prevention and 9.4% (14) remained on therapy. Conclusions: Physician-reluctance is not a dominant reason for poor uptake of endocrine prevention even by high-risk premenopausal women in a specialised risk management clinic. Many women are not eligible, and most elect for alternative options.